Live quantitative monitoring of mineral deposition in stem cells using tetracycline hydrochloride - Macri-Pellizzeri, Laura; De Melo, Nigel; Ahmed, Ifty; Grant, David M.; Scammell, Brigitte; Sottile, Virginie (Mary Ann Liebert, 2018)
The final stage of in vitro osteogenic differentiation is characterized by the production of mineral deposits containing calcium cations and inorganic phosphates, which populate the extracellular matrix surrounding the cell monolayer. Conventional histological techniques for the assessment of mineralization, such as Von Kossa and Alizarin Red S staining, are end-point techniques requiring cell fixation. Moreover, in both cases staining quantitation requires dye extraction which irreversibly alters the ECM conformation and structure, therefore preventing the use of the sample for further analysis.